Assessing the impact of a statewide effort to improve breastfeeding rates: A RE‐AIM evaluation of CHAMPS in Mississippi - Anne Merewood; Laura Burnham; Jacqueline Berger; Aishat Gambari; Cara Safon; Paige Beliveau; Tawanda Logan‐Hurt; Nathan Nickel (Wiley, 2022)
Abstract Communities and Hospitals Advancing Maternity Practices (CHAMPS) is a public health initiative, operating in Mississippi since 2014, to improve maternal and child health practices and reduce racial disparities in breastfeeding. Using the Reach, Effectiveness, Adoption, Implementation and Maintenance framework, this study assessed CHAMPS, which used a Quality Improvement intervention at hospitals, and engaged intensively with local community partners. The study team assessed outcomes through quantitative data (2014-2020) from national sources, Mississippi hospitals, community partners and CHAMPS programme records, and qualitative data from focus groups. With 95% of eligible Mississippi hospitals enrolled into CHAMPS, the programme reached 98% of eligible birthing women in Mississippi, and 65% of breastfeeding peer counsellors in Mississippi's Special Supplemental Nutrition Programme for Women, Infants and Children. Average hospital breastfeeding initiation rates rose from 56% to 66% (p < 0.05), the proportion of hospitals designated Baby‐Friendly or attaining the final stages thereof rose from 15% to 90%, and 80% of Mississippi Special Supplemental Programme for Women, Infants, and Children districts engaged with CHAMPS. CHAMPS also maintains a funded presence in Mississippi, and all designated hospitals have maintained Baby‐Friendly status. These findings show that a breastfeeding‐focused public health initiative using broad‐based strategic programming involving multiple stakeholders and a range of evaluation criteria can be successful. More breastfeeding promotion and support programmes should assess their wider impact using evidence‐based implementation frameworks.